Final answer:
To find (g-h)(a), subtract the function h(a) from g(a) and combine like terms. The result after performing the subtraction is option d) 6a + 4.
Step-by-step explanation:
To find (g-h)(a), we need to subtract the function h(a) from the function g(a). The functions are given by g(a)=4a−1 and h(a)=-2a−5. Subtracting these two functions would involve subtracting each corresponding term in the two functions. Perform the subtraction step by step as follows:
- Write the two functions: g(a) = 4a – 1 and h(a) = -2a – 5.
- Subtract h(a) from g(a): (g-h)(a) = (4a – 1) – (-2a – 5).
- Remove parentheses and change signs: (g-h)(a) = 4a – 1 + 2a + 5.
- Combine like terms: (g-h)(a) = 6a + 4.
Therefore, the correct answer for (g-h)(a) is option d)6a + 4.